New Lower Devonian Polygnathids (Conodonta) from the Spanish Central Pyrenees, with comments on the early radiation of the group - Martínez-Pérez, C.; Valenzuela-Ríos, J. I. (Journal of Iberian Geology, 2014)
The comprehensive study of six Pragian-lower Emsian (Lower Devonian) sections from the Spanish Central Pyrenees has yielded a rich assemblage of conodont faunas, highlighting an important succession of Polygnathus species. Among them, the presence of the biostratigraphical markers P. pireneae, P. kitabicus, P. excavatus excavatus and P. exc. 114 stands out. This conodont succession allows the identification of the Pragian/Emsian boundary and the early Emsian zones and subzones: the kitabicus Zone and the Lower and Middle excavatus subzones. It is also remarkable the presence of three new polygnathid species: P. aragonensis n. sp., P. carlsi n. sp. and P. ramoni n. sp. Additionally, P. pannonicus and P. sokolovi are also reported for first time in the Iberian Peninsula. According to all these records, the abundance and diversity of these species suggest that during this time interval an evolutionary radiation of the group took place, identifying two pulses during the early radiation of the group. The first one during the pireneae-kitabicus Zone, and a second one during the Lower excavatus Zone. The new data presented herein increase considerably the known paleobiodiversity of the genus during the Pragian-early Emsian interval in the Spanish Central Pyrenees and corroborates the presences of the most important early Emsian conodont markers used in other regions such us Europe, North Africa, Central Asia, Australia, and North America. ozonas Dc, E y F asociados al evento de enfriamiento global del Mioceno medio.